PRODUCTION RISK OF MORINGA (Moringa oleifera L.) IN THE RAINY AND DRY SEASONS - Ina Berlianty; Suyudi Suyudi; Nurul Risti Mutiarasari (Journal of Agri Socio Economics and Business, 2022)
This study aimed to determine and analyze the risk of moringa (Moringa oleifera L.) production in rainy and dry seasons at PT Moringa Organic Indonesia, Blora. The research method used is a case study method, using secondary data and time-series data and interviews with the company. The analytical tools used are coefficient variation (CV) and lower limit (L). The results show that the sources of production risk at PT Moringa Organic Indonesia consist of external and internal production risks, external production risks consist of weeds, disease, and seasons, while internal production risks are human resource risks. The calculation result of risk level of Moringa production for rainy season and dry season show the risk level of production in dry season has a high risk because it has a coefficient variation value greater than the rainy season. The lower limit of production (L) was obtained in the dry season, based on the lower limit values of the two seasons, indicating that the losses were lower than dry season during the rainy season.